(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
Poland and Hungary have played a pivotal role in the post-socialist democratic transformation, even in the field of elections and electoral legislation. The two countries differed from each other. Hungary opted for a mixed electoral system, in which the majoritarian component was dominant. Poland, instead, chose a proportional system. From a general standpoint, the judiciary system of the two countries – and, in particular, their constitutional courts – did not raise any particular objection to the basic guidelines of electoral legislation. The judicial intervention only took place occasionally, and more incisively in Hungary, when a significant departure from proclaimed principles occurred. This was particularly relevant with reference to the voting rights of citizens who live abroad.